ANALISIS HOSTING CAPACITY PADA JARINGAN TEGANGAN MENENGAH UNTUK SUPLAI DAYA LISTRIK DAERAH PEDESAAN - Budiantari, N.W.; Ariastina, W.G.; I.W.Sukerayasa, I.W.Sukerayasa (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i02.p5, 2022)
As technology advances, the use of electrical energy increases for this reason, energy conversion is needed, one of which is the installation of photovoltaic. Analysis hosting capacity on the distribution network serves to determine the flow of power when photovoltaic is installed and can analyze voltage, conductor loading, power loss, and good transformer loading when connected to the network.The analysis of hosting capacity on rooftop PV mini-grid spread over the distribution network is very useful for future planning if there is a massive energy transition that is implemented on rooftop PV mini-grid. The hosting capacity analysis on the distribution network was carried out in 2 scenarios, which were Scenario A for the Bangli feeder without being connected to the PLTS 1 MWp and Scenario B for the parameter B for the Bangli feeder being connected with the PLTS 1 MWp. The analyzed parameters included voltage, conductor loading, transformer loading and power losses in network. The results of the analysis showed that the distribution network hosting capacity is 40%, for both Scenario A and Scenario B.